Um estudo com egressos do curso Técnico em Eletrotécnica da ETEC Jaraguá - Galaverna, Carlos Henrique Saderio (2023)
This research aimed to investigate the reasons that led a group of former students of Professional Technical Education (Etec) at Centro Paulo Souza to choose the electrical engineering course at Etec Jaraguá, a school located on the outskirts of São Paulo, in addition to verifying – ten years after graduation – whether professional expectations were met. In investigating the conditions that influenced the process of “choosing” the researched subjects, we used the concepts of economic, cultural and social capital proposed by Bourdieu (1998). We start from the hypothesis that economic conditions, family practices and families' social and educational trajectories influenced individuals' decisions. To explain students' educational strategy in the social space, we employ the concepts of classification, reclassification and declassification (Bourdieu, 1998). Data collection occurred in two stages: firstly, through the use of a socioeconomic questionnaire, seeking to characterize the economic, cultural and social capital of those surveyed. In the second stage, we carried out interviews to investigate the mode of transmission of cultural capital and how this influenced the option for a technical course in electrical engineering. When retracing the social trajectory of the graduates, the data revealed that the low acquisition of capital made it impossible for them to make a fully conscious “choice” for the course. This option resulted from a strategy that aimed to quickly enter the job market in order to pay for higher education, an objective that was not achieved by a significant portion of those surveyed